DEVELOPMENT OF SOLAR POWERED STATIC WIRELESS CHARGING SYSTEM FOR ELECTRIC VEHICLES (International Journal of Engineering Management Science, 2024)
The introduction of electric vehicles to the modern world corresponds with the growing adoption of new technology in everyday life. Even with the usage of electric Nevertheless, a few restrictions are still in place. These include problems like overheating when charging, possible charging depletion, a lack of charging stations, and the expensive installation of such stations. This proposal suggests a wireless electric vehicle charging station with monitoring features in order to address these issues. The objectives include avoiding overcharging, keeping an eye on battery levels, guaranteeing cost-effectiveness, encouraging environmental friendliness, and situating charging stations in strategic locations around cities. The project's design especially addresses the problems of fuel dependence and environmental pollution by providing an electric vehicle charging infrastructure powered by solar energy. Worldwide interest in electric vehicles has grown, and they are increasingly becoming more prevalent. This project offers a creative remedy for EV charging, removing the need for cables, permitting charging while driving, and using solar energy to maintain the charging mechanism and functioning without the need for an external power source. A solar panel, battery, transformer, regulator circuitry, copper coils, AC to DC converter, Atmega controller, and LCD display are some of the parts that make up the system. The integration allows the system to demonstrate how electric vehicles may be charged wirelessly at charging stations. The LCD display eliminates the need to stop the car while it charges by giving real-time information on the entire cost. In conclusion, the project presents a forward-thinking method of integration and shows the feasibility of a solar-powered wireless charging system for electric automobiles.
Keywords: Solar Panel, Boost Converter, Battery, Transmitting Coil, Receiving Coill, Arduino uno, Voltage sensor